Transmission of tauopathy strains is independent of their isoform composition - Zhuohao He (Nature Portfolio, 2020)
Although normal human brains express 6 tau isoforms in equal ratio with 3 or 4 microtubule-binding repeat domains (3R and 4R), tau inclusions from different human tauopathy brains, now considered as different strains, have distinct isoform compositions and strain properties and the relationship between these two parts is unclear. Here the authors generate a new transgenic mouse line expressing 6 human tau isoforms with equal 3R and 4R ratios, recapitulate distinct human tau strains in mouse brains with similar isoform compositions and cell type specificities, and further show the strain transmission pattern is independent of its isoform composition.